The AI Revolution in Ophthalmology: Can Machine Learning Accurately Detect Glaucoma Progression? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Glaucoma, often termed the "silent thief of sight," is a leading cause of irreversible blindness worldwide. Its management hinges critically on the timely an...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning; Medical Ethics